2016
DOI: 10.1016/j.jasrep.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Maya turkey husbandry: Testing theories through stable isotope analysis

Abstract: Large gaps exist in our knowledge of ancient Maya turkey husbandry and management. Among the questions still needing to be addressed are: 1) when and where was the non-local wild turkey (Meleagris gallopavo) introduced to and adopted by the ancient Maya, and 2) did the ancient Maya also rear captive or tame populations of the indigenous ocellated turkey (Meleagris ocellata)? In this paper, we assess the potential of stable isotope analysis to address these questions. We employ stable carbon (δ 13 C) and nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 69 publications
(95 reference statements)
5
38
0
Order By: Relevance
“…were the only known domesticated animals in highland Chiapas during the Early Postclassic period. Both species have been recovered at lowland Maya sites in Guatemala and Belize, dating to the Middle Preclassic period (Wing 1978;Shaw 1991;Clutten-Brock & Hammond 1994;White et al 2001;Thornton et al 2012Thornton et al , 2016Thornton & Emery 2017;Manin et al 2018a). In pre-Columbian times, domestic dogs in the Maya culture area were eaten (Pohl 1990;Clutten-Brock & Hammond 1994) and used in sacrifices (Pollock & Ray 1957).…”
Section: Animal Husbandrymentioning
confidence: 99%
“…were the only known domesticated animals in highland Chiapas during the Early Postclassic period. Both species have been recovered at lowland Maya sites in Guatemala and Belize, dating to the Middle Preclassic period (Wing 1978;Shaw 1991;Clutten-Brock & Hammond 1994;White et al 2001;Thornton et al 2012Thornton et al , 2016Thornton & Emery 2017;Manin et al 2018a). In pre-Columbian times, domestic dogs in the Maya culture area were eaten (Pohl 1990;Clutten-Brock & Hammond 1994) and used in sacrifices (Pollock & Ray 1957).…”
Section: Animal Husbandrymentioning
confidence: 99%
“…Human dietary intervention results in diets substantially altered from wild controls, reflected in correspondingly distinct animal isotope compositions. For example, macaws penned at the pre-Hispanic site of Paquimé in northern Mexico [ 12 ], turkeys in the ancient Southwestern United States and in the Maya region [ 8 , 75 ], or lagomorphs kept in captivity in Teotihuacan [ 18 , 19 ] were identified isotopically because of their conspicuously elevated or even total reliance on C 4 based resources. Among domesticated dogs of the Maya, this increased reliance on C 4 resources correlated with a decrease in nitrogen isotope ratios, an indication that meat protein input decreased as reliance on agricultural maize increased [ 20 ].…”
Section: Stable Isotopesmentioning
confidence: 99%
“…Oxygen isotope ratios, expressed as δ 18 O carbonate , can be read from bone, tooth enamel, and tooth dentine. As the δ 18 O values varies by the water source an organism drinks (which in turn reflects the climate and geography of the region) and the organism’s physiology, oxygen isotope ratios can illuminate origin and migration patterns of humans and animals [ 8 , 23 , 76 78 ]. Throughout Mesoamerica, extensive work on oxygen and strontium isotopes on human skeletal remains have helped develop isoscapes of the regions studied [ 79 83 ].…”
Section: Stable Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the common turkey ( M. gallopavo ), the brightly plumed ocellated turkey ( M. ocellata ) is found within Mexico's Yucatan peninsula, and parts of northern Belize and Guatemala ( figure 1 ). While ocellated turkeys are not currently raised as domestic birds in the Yucatan, their potential captive rearing has long been discussed among zooarchaeologists and ornithologists, although this practice has not been conclusively demonstrated in the archaeological record [ 30 ]. Finally, previous aDNA research suggested that the domestic turkey of the SW USA was genetically distinct from the Mesoamerican lineage [ 19 ] with no evidence for trade of domestic turkey between the two regions.…”
Section: Introductionmentioning
confidence: 99%